2014
DOI: 10.1371/journal.pone.0107217
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Extracellular Ca2+ Induces Store-Operated Calcium Entry via Calcium-Sensing Receptors: A Pathway Contributes to the Proliferation of Osteoblasts

Abstract: AimsThe local concentration of extracellular Ca2+ ([Ca2+]o) in bone microenvironment is accumulated during bone remodeling. In the present study we investigated whether elevating [Ca2+]o induced store-operated calcium entry (SOCE) in primary rat calvarial osteoblasts and further examined the contribution of elevating [Ca2+]o to osteoblastic proliferation.MethodsCytosolic Ca2+ concentration ([Ca2+]c) of primary cultured rat osteoblasts was detected by fluorescence imaging using calcium-sensitive probe fura-2/AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 49 publications
3
44
0
1
Order By: Relevance
“…The increase in the concentration of calcium ions released from MTA over 3 days was ~0.7 mM and the average of increment of each day during experimental periods was ~0.3 mM in this culture system. Recently, osteoblast proliferation through CaSR and activation of phospholipase C in the condition of 2 mM extracellular calcium ions has been shown in primary rat calvarial cells 28) . Therefore, it was supposed that the calcium ions released from MTA might affect gene expressions of Runx2, type I collagen via CaSR.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the concentration of calcium ions released from MTA over 3 days was ~0.7 mM and the average of increment of each day during experimental periods was ~0.3 mM in this culture system. Recently, osteoblast proliferation through CaSR and activation of phospholipase C in the condition of 2 mM extracellular calcium ions has been shown in primary rat calvarial cells 28) . Therefore, it was supposed that the calcium ions released from MTA might affect gene expressions of Runx2, type I collagen via CaSR.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies have demonstrated that increased calcium levels activate PLC, finally resulting in the sustained elevation of calcium concentration (4). Activated PLC cleaves phosphatidylinositol 4,5-bisphosphate (PIP2), a phosphorylated derivative of phosphatidylinositol that is mainly located in the inner half of the plasma membrane lipid bilayer (5-9), into inositol trisphosphate (IP3) and diacylglycerol (DAG).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that Ca 2+ , dose‐dependently, enhances proliferation of MC3T3 and human periosteal derived stem cells [Chai et al, ]. It also was reported that elevation of extracellular Ca 2+ stimulates the proliferation of rat primary osteoblasts involving store‐operated calcium entry and phosphorylation of ERK1/2 induced by activation of calcium‐sensing receptors [Ma et al, ; Hu et al, ]. ERK1/2 phosphorylation also occurred when MC3T3‐E1 cells were treated with PO 4 3− in the presence of Ca 2+ , but not in its absence [Khoshniat et al, ].…”
mentioning
confidence: 99%